Risky behavior, personality traits and road accidents among university students - Ferreira, A. I.; Martinez, L. F.; Guisande, M. A. (European Journal of Education and Psychology, 2009)
The personality traits that mediate risky driving and accidents among university students drivers were investigated. Study 1 (N=132) tested for the relation between risky behaviors and personality (16PF-5 second order dimensions). Three factors were extracted concerning risky driving: driving errors of commission, distraction, and driving errors of omission. Individuals with low self-control and high levels of anxiety were more prone to commit distractive behavior and driving errors of omission. Low selfcontrol and high independence levels were associated with driving errors of commission. In study 2 (N=540), we tested if the number of road accidents for which an individual has been responsible was related to risky driving behavior. Drivers who committed more accidents presented higher scores in three new risky driving factors obtained: reckless driving, impaired concentration and division of attention.